The spiritual and moral growth of young children through collaborative sports with older individuals - Pronina A.N.; Budyakova T.P. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to examination of the influence of collaborative sports activities with older individuals on the personal growth of pre-schoolers and early school-age children. Methods and structure of the study. The observation was conducted as part of the training sessions for athletes of various ages, including the charity table tennis tournament «Steel Tree-2024». The study involved 23 participants, including 14 retirees and 9 children from preschool and primary school. Four aspects were chosen as the focus of the observation: cooperation, encouragement, respect, and appreciation. Results and conclusions. It was discovered that during joint training and competitions, preschoolers and younger schoolchildren exhibited positive behavioral responses both towards their peers and towards the older participants, but these responses were more pronounced towards the elderly. There were no instances of age-based discrimination, which is often observed in society when it comes to the elderly. The criteria for respect were the athletic abilities and experience of the older competitors. The age factor was only evident in the interactions between the adults and the children, where the adults sought to provide moral support to the younger athletes. In response, there was not only respect, but also gratitude, which contributed to the spiritual and moral development of the children.